Sam : The Sound of "S" - Flanagan, Alice K. ([Chanhassen, Minn.] : Child's World, Inc., 2000)
Simple text and repetition of the letter "s" help readers learn how to use this sound.
Keywords: Crabs -- Fiction; Alphabet